1995
DOI: 10.2166/wst.1995.0262
|View full text |Cite
|
Sign up to set email alerts
|

Solids retention time in heterotrophic and nitrifying biofilms in a biofilm airlift suspension reactor

Abstract: The solids retention time in biofilms was determined by using fluorescent microbeads as solid tracers. Attachment to and detachment from the biofilms, as well as surface concentration of the microbeads were measured. The surface concentration depended on the surface characteristics of the biofilms. The attachment rate was equal in three experiments and dependent on hydrodynamic conditions in the reactor. In all cases the detachment rate was much smaller than the attachment rate and larger than the average soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…water. Studies on a rotating annular reactor or an airlift suspension reactor also showed lower adsorption efficiencies of biofilms in the diurnal time frame (13,43,44). Reactors in these studies worked in a continuous mode, which entails lower and more constant particle concentrations than the batch mode.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…water. Studies on a rotating annular reactor or an airlift suspension reactor also showed lower adsorption efficiencies of biofilms in the diurnal time frame (13,43,44). Reactors in these studies worked in a continuous mode, which entails lower and more constant particle concentrations than the batch mode.…”
Section: Discussionmentioning
confidence: 89%
“…These filters comprise mature biofilms with highly dynamic microbial populations, for which particulate material constitutes an important carbon resource (22,28). Consequently, the interception of particles by the biofilm is essential for the performance of bioreactors (44). Since particles tend to accumulate hazardous pollutants at their surface, their removal from wastewater is all the more important (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the biofilms, obtained within 7 d of cultivation in the present study had the structure that is known to develop under the substrate regime that used in the experiments (Costerton et al, 1995;Yang et al, 2000). Features of this structure include nonuniform thickness, patchyness, and presence of pores up to 100 Jim in diameter allowing penetration of particles into the biofilm and water flow below its surface (Costerton et al, 1995;van Benthum et al, 1995). Both heterotrophically grown and nitrifying biofilms showed this type of structure, which should allow the penetration of SRB into deeper regions of the biofilms, in the vicinity of anoxic zones.…”
Section: Discussionmentioning
confidence: 96%
“…The biomass density in granules was set to 80000 gCOD/m 3 . [26] This represents a concentration in the granules of 60000 gVSS/m 3 for a conversion factor of 0.75 gVSS/gCOD. [27] Porosity was assumed constant (80%) throughout the granule.…”
Section: Granular Sludgementioning
confidence: 99%